"Inhuman!" Transgressions: A Picture of Torture in Iffland's the Foresters. Issue 2 (2nd June 2022) - Clark, Sophia Y.
Abstract: As a playwright, August Wilhelm Iffland is best known for his sentimental domestic plays and dramas which enjoyed wild popularity amongst theater audiences from the late eighteenth century until about the early to mid-nineteenth century. One of Iffland's earliest successes, The Foresters (1785), draws on a criminal case involving interrogational torture for a late-stage conflict in act five. Iffland's source material for The Foresters was the author's first dive into the popular practice of adapting the contents of criminal court cases into literary or theatrical narratives and announcing them as such. This essay analyzes the play's engagement with contemporary discourses on legal reform in the 1780s, and the extent to which Iffland's early work actually explores these problems. By staging serious legal themes such as torture in a domestic, middle-class setting for an enlightened audience, The Foresters allows us a glimpse at how popular plays might try to make sense of the complex relationship between the progressive legal reform efforts in the German territories and the legacy of seemingly outdated legal institutions.